Does Training Work? Re-Examining Donor-Sponsored Training Programs in Developing Countries - Nelson, Mark (World Bank, Washington, DC, 2012)
This article examines the available evidence about training as an instrument of capacity development and asks whether it works and under which conditions it is most optimally pursued. The first part of the paper considers evidence from the World Bank and other international donors, which spend considerable sums on training in developing countries. The second part of the paper looks at the record of private sector firms to see what can be learned from company training programs, which have tended to be better documented and followed from a cost-effectiveness standpoint. The article then considers what conclusions from the private sector can help us toward a better understanding of the optimal conditions for training in a development context.